Muscle mechanical properties of strength and endurance athletes and changes after one week of intensive training. (October 2016) - de Paula Simola, Rauno Álvaro; Raeder, Christian; Wiewelhove, Thimo; Kellmann, Michael; Meyer, Tim; Pfeiffer, Mark; Ferrauti, Alexander
Abstract: The study investigates whether tensiomyography (TMG) is sensitive to differentiate between strength and endurance athletes, and to monitor fatigue after either one week of intensive strength (ST) or endurance (END) training. Fourteen strength (24.1 ± 2.0 years) and eleven endurance athletes (25.5 ± 4.8 years) performed an intensive training period of 6 days of ST or END, respectively. ST and END groups completed specific performance tests as well as TMG measurements of maximal radial deformation of the muscle belly (Dm), deformation time between 10% and 90% Dm (Tc), rate of deformation development until 10% Dm (V10) and 90% Dm (V90) before (baseline), after training period (post1), and after 72 h of recovery (post2). Specific performance of both groups decreased from baseline to post1 ( P  < 0.05) and returned to baseline values at post2 ( P  < 0.05). The ST group showed higher countermovement jump ( P  < 0.05) and shorter Tc ( P  < 0.05) at baseline. After training, Dm, V10, and V90 were reduced in the ST ( P  < 0.05) while TMG changes were less pronounced in the END. TMG could be a useful tool to differentiate between strength and endurance athletes, and to monitor fatigue and recovery especially in strength training.